(untitled) (Research, Society and Development, 2021)
Introduction: The mandibular buccal bifurcation cyst (MBBC) is a cystic lesion of odontogenic origin, which occurs in relation to the buccal surface of the first and second mandibular molars, with clinical, radiographic and histological characteristics similar to other pathological entities of the mandible related to inflammatory processes. Clinically, they usually present as an inflammation in the vestibule of the vital first and second molar region, with the presence of deep periodontal pockets. There is controversy regarding the exact etiology and treatment, so the present study aims to discuss the clinical and radiographic characteristics of QBBM, the differential diagnosis and its treatment, which differs whether or not cystic enucleation includes tooth extraction. Methodology: A systematic review of the literature was carried out in different digital databases, collecting relevant information that justifies the findings of this case. Results: In this particular case, certain characteristics such as enamel projection in the bifurcation area was a clear indication of MBBC. The treatment of choice was the enucleation of the cyst with the extraction of the tooth.